Sustainable development of tourism in the Maldives - Ćirić, Bojan; Vladušić, Ljubica (Hotel and Tourism Management, 2017)
Small island countries tend to develop their economy by means of tourism and thus overcome poverty. However, such a tendency often leads to difficulties in achieving a balance between economic development and enviromental protection. Though Maldives promote themselves as a sustainable destination, during the last couple of years problems started to emerge idicating that there is no harmony among social, economic and ecological sustainability and that each and every of these segments contains negative effects that can have major implications on the future development of tourism in this island country.